Gulf War illness associated with abnormal auditory P1 event-related potential: Evidence of impaired cholinergic processing replicated in a national sample. (30th January 2019) - Tillman, Gail D.; Spence, Jeffrey S.; Briggs, Richard W.; Haley, Robert W.; Hart, John; Kraut, Michael A.
Highlights: We replicated a previous study using a broader sample of Gulf War veterans. Hyperarousal and P1 findings were replicated. Gulf War illness syndromes 1, 2, and 3 reported higher hyperarousal than controls. Syndromes 2 and 3 showed significantly higher P1 amplitudes than Syndrome 1. The P1 findings are consistent with cholinergic system disruption in ill veterans. Abstract: Our team previously reported event-related potential (ERP) and hyperarousal patterns from a study of one construction battalion of the U.S. Naval Reserve who served during the 1991 Persian Gulf War. We sought to replicate these findings in a sample that was more representative of the entire Gulf War-era veteran population, including male and female participants from four branches of the military. We collected ERP data from 40 veterans meeting Haley criteria for Gulf War syndromes 1–3 and from 22 matched Gulf War veteran controls while they performed an auditory oddball task. Reports of hyperarousal from the ill veterans were significantly greater than those from the control veterans, and P1 amplitudes in Syndromes 2 and 3 were significantly higher than P1 amplitudes in Syndrome 1, replicating our previous findings. Many of the contributors to the generation of the P1 potential are also involved in the regulation of arousal and are modulated by cholinergic and dopaminergic systems—two systems whose dysfunction has been implicated in Gulf War illness. These differences among the three syndrome groups where their means were on either side of controls is a replication of our previous ERP study and is consistent with previous imaging studies of this population.